Perancangan User Experience dan Gamifikasi Pada Aplikasi Pembelajaran Online Jurusan Sistem Informasi Menggunakan Octalysis Framework - Vivian Dzikriany Azis; Herman Tolle; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The flexibility of learning activities is one of the needs for students and educators in the era of technology that has been growing rapidly. Mobile-based independent learning is expected to support learning activities in lectures intended for students studying at the Information Systems Department of the Faculty of Computer Science, Universitas Brawijaya. There is no adequate platform for online learning. Therefore, new solutions and innovations are needed for making online learning applications using the MOOC concept. The design of user experience that is carried out also has elements of improved gamification in order to provide user experience that can increase student motivation. The addition of the gamification element must begin with the identification of the user profile using the Octalysis Framework. The design will be made in the form of high-fidelity prototypes using the Human-centered Design (HCD) method. The results of the evaluation using Techniques for Evaluating User Experience in e-Learning (TUXEL) yielded 13 problems on Usability Inspection in the Login, General Interface, and Assignment categories. In Pedagogical Usability found 8 problems in the category of Help & Documentation, LMS Learnability, Learning Through The LMS, and LMS Flexibility. The User Experience Evaluation shows positive values ​​in the attractiveness, dependability, efficiency, novelty, stimulation, and normal values ​​in the perspicuity dimension.